Frequency and Risk Factors for Live Discharge from Hospice. Issue 8 (13th March 2017) - Russell, David; Diamond, Eli L.; Lauder, Bonnie; Dignam, Ritchell R.; Dowding, Dawn W.; Peng, Timothy R.; Prigerson, Holly G.; Bowles, Kathryn H.
Abstract : Objectives: To report frequencies and associated risk factors for 4 distinct causes of live discharge from hospice. Design: Retrospective cohort study using electronic medical records of hospice patients who received care from a large urban not‐for‐profit hospice agency in New York City during a 3‐year period between 2013 and 2015 (n = 9, 190). Results: Roughly one in five hospice patients were discharged alive (21%; n = 1911). Acute hospitalization was the most frequent reason for live discharge (42% of all live discharges; n = 802). Additional reasons included elective revocation to resume disease‐directed treatments (18%; n = 343), disqualification (14%; n = 271), and service transfers or moves (26%; n = 495). Multinomial logistic regression analyses revealed that risk for acute hospitalization was higher among younger patients (age AOR = 0.98 [95% CI = 0.98–0.99] P < .01), racial/ethnic minorities (Hispanic AOR = 2.23 [CI = 1.82–2.73] P < .001; African American OR = 2.46 [CI = 2.00–3.03] P < .001; Asian/other OR = 1.63 [CI = 1.25–2.11] P < .001), and patients without advance directives (AOR = 1.41 [95% CI = 0.98–0.99] P < .001). Disqualification occurred much more frequently among patients with non‐cancer diagnoses, including dementia (AOR = 13.14 [95% CI = 7.96–21.61] P < .001) and pulmonary disease (AOR = 11.68 [95% CI = 6.58–20.74] P < .001). Transfers and service moves were more common among Hispanics (AOR = 1.56 [95% CI = 1.45–2.34] P < .001), African Americans (AOR = 1.35 [95% CI = 1.03–1.79] P < .05), patients without a primary caregiver (AOR = 1.35 [95% CI = 1.09–1.67] P < .001), and those without advance directives (AOR = 1.30 [95% CI = 1.07–1.58] P < .01). Conclusion: Further research into factors that underlie live discharge events, especially acute hospitalization, is warranted given their cost and burden for patients/families. Hospices should develop strategies to address acute medical crises and thoroughly evaluate patients' suitability, unmet needs, and knowledge about end‐of‐life issues at the time of hospice enrollment, especially for those with non‐cancer diagnoses.